2010
DOI: 10.1007/s11205-010-9648-x
|View full text |Cite
|
Sign up to set email alerts
|

Spouse “Together Time”: Quality Time Within the Household

Abstract: Time-use, Quality of life, Working time, Family life, Time together,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Both husbands’ and wives’ employment—especially long work hours—are negatively associated with marital interaction (e.g., Amato et al, 2007; Booth, Johnson, White, & Edwards, 1984; Roeters & Treas, 2011; White, 1983; but see Roeters & Treas, 2011). From the time use literature we know that individuals in dual-earner couples spend less time with their spouse than individuals in single-earner couples (Kingston & Nock, 1987; Presser, 2000; Voorpostel et al, 2009) as do individuals in couples in which one member works on the interview (i.e., diary) day (Barnet-Verzat et al, 2010; Dew, 2009; Glorieux, Minnen, & van Tienoven, 2011; Polivka, 2008; Wight et al, 2008) and in couples with large differences in paid work hours (Mansour & McKinnish, 2014). For example, Kingston and Nock (1987) drew on a small sample of couples from 1981 and showed that dual-earner couples spend 30 minutes less in total spousal time than single-earner couples.…”
Section: Work Parenting and Couples’ Shared Timementioning
confidence: 99%
See 1 more Smart Citation
“…Both husbands’ and wives’ employment—especially long work hours—are negatively associated with marital interaction (e.g., Amato et al, 2007; Booth, Johnson, White, & Edwards, 1984; Roeters & Treas, 2011; White, 1983; but see Roeters & Treas, 2011). From the time use literature we know that individuals in dual-earner couples spend less time with their spouse than individuals in single-earner couples (Kingston & Nock, 1987; Presser, 2000; Voorpostel et al, 2009) as do individuals in couples in which one member works on the interview (i.e., diary) day (Barnet-Verzat et al, 2010; Dew, 2009; Glorieux, Minnen, & van Tienoven, 2011; Polivka, 2008; Wight et al, 2008) and in couples with large differences in paid work hours (Mansour & McKinnish, 2014). For example, Kingston and Nock (1987) drew on a small sample of couples from 1981 and showed that dual-earner couples spend 30 minutes less in total spousal time than single-earner couples.…”
Section: Work Parenting and Couples’ Shared Timementioning
confidence: 99%
“…The literature consistently shows that parents spend less time with one another in leisure—and more generally—than nonparents (Barnet-Verzat et al, 2010; Dew, 2009; Glorieux et al, 2011; Hill, 1988; Mansour & McKinnish, 2014; Voorpostel et al, 2009). The transition to parenthood initially reduces leisure shared with a spouse (Claxton & Perry-Jenkins, 2008) as couples’ shared time shifts from leisure as a couple to leisure as a family (Huston & Vangelisti, 1995) and to more instrumental tasks following the birth of a child (Clements & Markman, 1996; Huston, McHale, & Crouter, 1986).…”
Section: Work Parenting and Couples’ Shared Timementioning
confidence: 99%
“…Spending time together as families requires solving the problem of conflicting work schedules. Working night shifts or weekend shifts exacerbates schedule conflicts within families (Boulin & Lesnard, 2016;Glorieux, Minnen, & van Tienoven, 2010;Täht & Mills, 2016). Because couples have to synchronize their work schedules to spend time together, the more complicated such schedules are, the greater the challenge is for togetherness.…”
Section: Work Constraints and Time Spent With Family Membersmentioning
confidence: 99%
“…The with whom information has been slightly more often used to study time with children (Wight, Raley, & Bianchi, 2008). Time-use studies have stressed the importance for families and couples of time together, without empirically testing its importance (Glorieux et al, 2010;Lesnard, 2008). One of the main reasons for this is the lack of data on partnership quality or family cohesion in time-use surveys.…”
Section: Measurementsmentioning
confidence: 99%
“…Similarly, decreased levels of work-family conflict [1,37] and domestic labour [31], increased quality time with family and friends [32,53], and strong sense of belonging to community tend to improve social contact and life satisfaction [50].…”
Section: Intervenining Conceptsmentioning
confidence: 99%